Versatile NTP recognition and domain fusions expand the functional repertoire of the ParB-CTPase fold beyond chromosome segregation - Jovana Kaljević; Kirill V. Sukhoverkov; Katie E. Johnson; Antoine Hocher; Tung B. K. Le (Proceedings of the National Academy of Sciences, 2025)
Nucleotide triphosphate (NTP)-dependent molecular switches regulate essential cellular processes by cycling between active and inactive states through nucleotide binding and hydrolysis. These mechanisms were long thought to rely exclusively on ATPase or GTPase proteins, until the discovery of CTPase activity in the bacterial chromosome segregation protein ParB. In the ParAB S system, CTP binding enables ParBs’ accumulation around the centromere-like parS DNA sites to activate the ATPase ParA, thereby facilitating chromosome partitioning to daughter cells. CTP hydrolysis then releases ParB from DNA for recycling. This discovery uncovered a new regulatory principle, but the broader diversity of proteins employing a CTPase mechanism remains unclear. Here, we conduct a large-scale survey of proteins harboring the ParB-CTPase fold across bacteria, archaea, bacteriophages, and eukaryotes. While many ParB-like proteins follow the canonical ParAB S organization with ParA partners, we also identify numerous orphan homologs encoded outside of the parAB operon, frequently linked to mobile genetic elements that may have driven their rapid diversification. The ParB-CTPase folds in these divergent proteins are often fused to lineage-specific domains with diverse predicted biological activities. We further demonstrate that while many homologs retain CTP-binding, others instead bind ATP or GTP, revealing a broader spectrum of nucleotide specificities than previously appreciated. Our findings establish the ParB-CTPase fold as a widely distributed and evolutionarily versatile NTP-binding module, repeatedly co-opted through domain fusion and shifts in nucleotide specificity to enable functions far beyond the classical ParAB S -mediated DNA segregation.